"Learning Together": Braiding Indigenous and Western Knowledge Systems to Understand Freshwater Mussel Health in the Lower Athabasca Region of Alberta, Canada. Issue Volume 39:Issues 2(2019) (June 2019) - Hopkins, Debra; Joly, Tara L.; Sykes, Harvey; Waniandy, Almer; Grant, John; Gallagher, Lorrie; Hansen, Leonard; Wall, Kaitlyn; Fortna, Peter; Bailey, Michelle
Fort McMurray Métis Elders and land users have observed a decrease in the population density of freshwater mussels (known locally as clams; Unionidae) in the lower Athabasca region (LAR) in recent decades. A community-based participatory research (CBPR) approach, braided with Indigenous Knowledge, is used as a guiding framework to facilitate partnerships and create safe, ethical spaces across diverse knowledge systems to address questions about freshwater mussel health in a locally relevant and culturally appropriate way. Opportunities for Elders and land users to travel along the Athabasca and Clearwater rivers in search of freshwater mussels allowed for the renewal of personal and cultural relationships to place that was braided with the study of parameters relevant to Western science. Our search revealed the presence of fat muckets ( Lampsilis siliquoidea ), with a limited number of giant floaters ( Anodonta grandis ), in our study area. However, delineating the types of species present is only the beginning of our work to understand freshwater mussel health in the LAR. We present a methodological discussion that demonstrates the importance of prioritizing Indigenous Knowledge to answer questions that may not have been considered within Western knowledge systems and shows how diverse ways of knowing can be braided to create new learnings together. "Learning together, " in practice, means recognizing that each person has knowledge and skills to contribute, which also involves shared decision making. We maintain that by "learning together, " complex problems can be understood in ways that are more meaningful and insightful than they would be if Indigenous communities, government scientists, or research consultants studied them alone.